Runoff Forecasting and Its Application in Reservoir Operation and Flood Warnings in Nepal - Khanal, Anup; Timalsina, Netra Prasad; Alfredsen, Knut (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Runoff forecasting is a very useful tool in hydrology to predict runoff based on a weather forecast. In developed countries, the method is also currently used for flood forecasting, and to predict runoff for hydropower reservoirs and water allocation for irrigation. But this is not the case in Nepal. The purpose of this paper is to demonstrate how to set up a system for runoff forecasting for a Nepalese catchment and illustrate how these procedures could be utilized in reservoir operation and flood warnings. This paper provides the necessary steps for implementing such a system in Nepal, including the selection of a meteorological forecast model, bias correction of the model output, HBV model set up, and runoff forecast simulation. DOI: http://dx.doi.org/10.3126/hn.v15i0.11288 HYDRO Nepal Journal Journal of Water Energy and Environment Volume: 15, 2014 July Page: 23-29